Entwicklung das Bilderbuch Als Lernmedien Im Deutsch Leseverstehen Fertigkeit Klasse XI MAN 2 Bojonegoro - LINGGA P, PRADITA (LATERNE, 2014)
Reading is not memorized word by word or sentence by sentence contained in the passage, which is more important in the process of reading comprehension is the message, information, facts or main ideas reading well. Reading is a skill, which the reader must perform various activities in accordance with the demands of the text. Focus on the issues that will be discussed in this study, there are four things, including: (1) How to develop a picture book as a medium of learning the German language to high school students of class XI? (2) What is the feasibility of the media picture book based on the validation of the matter experts and media experts? (3) How do students’ opinions about the media-shaped learning the German language story book? (4) How do the test results of students using the picture book medium? The purpose of this study was: (1) Develop a picture book as a medium of learning the German language to high school students of class XI. (2) Determine the feasibility of the media picture book based on the validation of the matter experts and media experts. (3) Knowing what students say about learning media shaped storybook the German language. (4) Knowing the test results of students using the picture book medium. The discussion in this study using a model of the development of Research and Development (R & D) Sugiyono, which include (1) potential problems, (2) data collection, (3) product design, (4) validation of design and materials, (5) revision of product design, and ( 6 ) the trial product. Based on the above discussion, the results of the development of German language picture book media declared fit for use. Results of Validation media: 91.6 %. Matter expert validation results: 92.3 %. The results of a small trial group: 77.7 %. The results of testing a large group of 85.9 %. Average overall validation validator is 86.8 %. Validation of the results that have been made stating that the media picture book in the German language skills of reading comprehension for students of class XI is very well qualified for use. Keywords: Development Picture books, Reading Comprehension Skills